Applying a modified aluminum sulfate solution in the processes of drinking water preparation - Dushkin, Stanislav; Shevchenko, Tamara (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports a study on the application of aluminum sulfate solution, modified by the magnetic field and electrocoagulation, in the processes of drinking water preparation. The modification of the coagulant solution makes it possible to intensify water purification processes, to reduce reagent consumption by 25–30 %. It has been found that a dose of the modified aluminum sulfate solution of 28–30 mg/dm3 improves the efficiency of removal of suspended substances and coloration by 35–40 %. The dosage of the conventional reagent solution was 40 mg/dm3 while reaching the same purification parameters. Modifying a solution of aluminum sulfate with the magnetic field and electrocoagulation increases the hydraulic size of the coagulated suspension. A change in the hydraulic size in the suspension has been studied at different periods of the year. In winter, when treating water with the modified aluminum sulfate solution, there a decrease in the suspension content whose hydraulic size is 0.1 mm/s and less, from 89 % to 22 %. In this case, the content of suspended substances at settling decreases from 8.5–12.5 mg/dm3 to 5.6–8.3 mg/dm3. In spring, when using the modified coagulant solution, the content of suspension whose size is 0.1 mm/s and less decreased from 55 % to 15 %. In summer, there is an increase in the content of suspension whose size is 0.3–0.5 mm/, from 58 % (a conventional reagent solution) to 66 % (the modified reagent solution). This indicates an intensification of the coagulation of impurities and the clarification of water. The experimental data testify to an increase in the effectiveness of discoloration of natural low-turbid colored water to 63.3–63.9 % for the modified reagent solution at 45.5 % for a conventional reagent solution. A change in the bacteriological parameters has been determined: the effectiveness of the decrease in a microbial number grows from 11.6‒18.7 % to 18.6–25.1 %. In terms of a coli-index, the efficiency of purification grows from 16.6‒23.1 % to 23.0–29.5 %